The measurement of vaginal fluid creatinine aids in the diagnosis of preterm membrane rupture - Neda Hamdolahpour; Tahereh Behroozi-lak; Sonia Sadeghpour (Health Science Monitor)
Background & Aims: Introduction: Pre-labour rupture of membranes is a critical obstetric condition, presenting an important contribution to maternal and neonatal morbidity and mortality. This study aims to investigate the diagnostic value of vaginal fluid creatinine in the identification of PROM. Materials & Methods: In the present descriptive-analytical study, 150 pregnant women were recruited and randomly assigned to three groups: confirmed PROM (n=50), suspected PROM (n=50), and healthy controls (n=50). Vaginal fluid samples were collected and analyzed for creatinine concentration using the Jaffe technique. Data were analyzed with SPSS version 16, employing ANOVA and post hoc tests. Results: Mean creatinine level of vaginal fluid was significantly higher in the PROM group compared with the control group (p < 0.05). Tukey post hoc test showed significant creatinine level groupings between PROM cases and controls. Maternal age, gestational age, and fetal weight did not show a significant correlation with creatinine levels (p > 0.05). Creatinine testing demonstrated higher diagnostic accuracy compared to the Fern test with a moderate correlation rate of 54%. Conclusion: The measurement of creatinine in vaginal fluid is an inexpensive, quick, and dependable diagnostic test for PROM, which is superior to the Fern test. Vaginal creatinine testing may also enhance maternal and neonatal outcomes due to the timeliness and accuracy of early diagnosis of PROM.